Injectable, Adhesive, and Self-Healing Composite Hydrogels Loaded With Oxybutynin Hydrochloride for the Treatment of Overactive Bladder in Rats - Sun, Peng; Wang, Zheng; Wu, Tong; Zuo, Shishuai; Huang, Xiaoyu; Cui, Zilian; Zhang, Dong (Frontiers in Bioengineering and Biotechnology, 2022)
Object: The aim of this study was to prepare injectable, adhesive, and self-healing composite hydrogels loaded with oxybutynin hydrochloride and verify its function in the treatment of overactive bladder. Method: The ultraviolet (UV) absorption of oxybutynin (Oxy) in the solution was detected using a UV spectrophotometer at 233 nm, and the cumulative drug release was calculated using Origin software. L929 mouse fibroblasts were used to test cell adhesion to OCP50 and OCP100 hydrogels. Both FT-IR and NMR overactive bladder demonstrated that Dex was oxidized to PDA with aldehyde groups. Urodynamic examinations were performed 24 h after intraperitoneal injection in the rat model. The relative expression levels of Orai1 and STIM1 were detected by western blot (WB) and QPCR. Results: After loading Oxy, the shear adhesion under the wet conditions of OCP50 and OCP100 was higher than CP50 and CP100 (p < 0.05), and both were suitable for intravaginal administration. After 72 h of release, oxybutynin released 82.8% in OCP100 hydrogel and 70% in OCP50. Compared to the model, OCP50, CP100, and OCP100 relieved the overactive bladder and inhibited the expression of Orail and STIM1. Conclusions: Oxybutynin hydrogel could provide relief to overactive bladder by decreasing the expression of Orail and STIM1 in rats.